Analysis of Non-Agricultural Economic Growth Rates in Tanah Jawa District, Simalungun Regency - Christin Natalia Sianipar (Institute of Computer Science (IOCS), 2022)
Analysis of Non-Agricultural Economic Growth Rates in Tanah Jawa District Simalungun . The purpose of this study was to determine and observe the factors that become the rate of non-agricultural economic growth in Tanah Jawa District. To find out and observe the influence of the non-agricultural sector on the rate of economic growth in Tanah Jawa District. This research was conducted in Tanah Jawa District, from January to March 201 9 . This research is included in the type of observation, namely to identify its role and influence with an area. This type of research is descriptive quantitative, so that the research presents a description of the condition of various non-agricultural sectors to be determined as the base sector in Tanah Java District. The results of this study are that the non-agricultural sector in the rate of economic growth deserves to be used as a mainstay sector or referred to as the basic sector because all PAD sectors are: restaurant tax 1.54, excavation C 1.09, HO (nuisance permit) 1.87, bottom water tax land 1.04 and advertising tax 3.27. From the results of the LQ calculation that there are no non-base sectors. The occurrence of the rate of non-agricultural economic growth can be realized from the results of the number of food and beverage businesses that there is an increase in the types of food/beverage businesses, grocery stall businesses, restaurant businesses, coffee shop businesses and meatball stall businesses. The rate of economic growth in Tanah Jawa Subdistrict in the last year has increased as seen from the addition of the number of workers, and the development of trade can be seen from the increase in the number of trading businesses so that regional development can be realized in the Tanah Jawa Subdistrict.